Characterization of membrane lipids and, Changes therein during desiccation and rehydration of the resurrection plant Xerophyta humilis (Bak) Dur and Schinz - Tshabuse, Freedom (Department of Molecular and Cell Biology, 2018)
Drought is the primary challenge facing agricultural productivity and food sustainability productivity in Africa and many parts of the world. Very few higher plants, including crop plants, can survive periods of extended water loss. However, a small group of angiosperms, termed resurrection plants are able to lose up to 95% of their cellular water content in vegetative tissue upon extended periods of water, remain in an air-dry for months to years and regain full metabolic activity in the same tissue upon re-watering. The aim of this study was to investigate the changes in acyl chain composition within the major glycerophospholipids (in total and chloroplast suspension) and galactolipids (chloroplast suspension) at different stages of dehydration and rehydration treatments in the resurrection plant Xerophyta humilis (Bak) Dur and Schniz. This was done in order to ascertain their roles during acquisition of desiccation tolerance in X. humilis. The galactolipids and glycerophospholipids acyl chain compositions were determined by multiple reaction monitoring (MRM) mass spectrometry. The glycerophospholipids profiles from total leaves and roots lipid extracts showed an increased representation of unsaturated molecular species such as 18:3/18:3 (in leaves) and 18:3/18:2 (in leaves and roots) during dehydration, with a decrease in saturated and mono-saturated molecular species such as 16:0/16:0. Rehydration was associated with the opposite trend. Furthermore, increased representation of molecular species with unusual fatty acids were observed during dehydration, with the odd-numbered fatty acids such as 15:0, 17:0 and 19:0 increasing during dehydration and decreasing during re-watering. On the other hand, the 23:0 and 25:0 fatty acids decreased during dehydration and increased upon rehydration. Within the chloroplast profiles, the galactolipids (i.e. monogalactosyldiacylglycerolipids and digalactosyldiacylglycerolipids) showed maintenance of 18:3/18:3 and 18:3/18:2 molecular species during dehydration and rehydration. The phosphatidylglycerolipids profiles in the chloroplast, together with the uncommon chloroplastic glycerophospholipids such as phosphatidylethanolamine, phosphatidylcholine and phosphatidylinositol also showed an increase in the unsaturated molecular species during dehydration and decrease upon rehydration. Taken together, our data suggest that water deficit in X. humilis roots and leaves induce fatty acid unsaturation, as well as production of uncommon fatty acids. These unsaturated fatty acids may aid in maintaining membrane integrity during dehydration. This study shows that changes in lipid composition are part of the desiccation tolerance strategies used by X. humilis.